FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN KLAIM BPJS DI PUSKESMAS TELAGA BIRU KABUPATEN GORONTALO TAHUN 2025 - Pratiwi Putri Mamula; Rismunandar Katili; Merlin Abd Rahman (Universitas Muhammadiyah Klaten, 2026)
The implementation of the Social Security Administrative Body (BPJS), as a government agency responsible for administering the National Health Insurance (JKN), plays a crucial role in providing comprehensive and accessible healthcare services. Capitation funds refer to a prospective payment system in which monthly payments are made in advance to healthcare facilities. Primary healthcare centers receive predetermined capitation payments from BPJS Kesehatan, disbursed upfront regardless of the volume or type of services rendered. Puskesmas Telaga Biru experiences several factors that contribute to the decline in capitation. The general objective of this study is to identify the factors influencing the decrease in BPJS claims at Puskesmas Telaga Biru. This research employed a descriptive method with a qualitative approach. The study was conducted at Puskesmas Telaga Biru from June 12 to July 12, 2025, using interview and observation techniques. The findings reveal several factors contributing to the capitation decline at Puskesmas Telaga Biru, including incomplete medical record documentation, reduced patient visits and a high number of patient transitions, unforeseen financial burdens, a decrease in registered participants, and inadequate infrastructure and facilities. Therefore, these factors should be taken into account by Puskesmas Telaga Biru to optimize capitation management and ensure the delivery of maximum healthcare services to the local community.